2020
DOI: 10.1126/scitranslmed.aba4434
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of KSP in preclinical models of high-risk neuroblastoma

Abstract: Neuroblastoma is a childhood malignancy with often dismal prognosis; relapse is common despite intense treatment. Here, we used human tumor organoids representing multiple MYCN-amplified high-risk neuroblastomas to perform a high-throughput drug screen with approved or emerging oncology drugs. Tumor-selective effects were calculated using drug sensitivity scores. Several drugs with previously unreported anti-neuroblastoma effects were identified by stringent selection criteria. ARRY-520, an inhibitor of kinesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
1
16
0
1
Order By: Relevance
“…S1 ). In a recent drug screen, we assessed drug sensitivity scores for various compounds against three neuroblastoma PDX models (LU-NB-1, LU-NB-2, and LU-NB-3) relative to human healthy bone marrow cells [17] . There was a more than three-fold increase in the effect of rigosertib on neuroblastoma cells relative to the effect on bone marrow control cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1 ). In a recent drug screen, we assessed drug sensitivity scores for various compounds against three neuroblastoma PDX models (LU-NB-1, LU-NB-2, and LU-NB-3) relative to human healthy bone marrow cells [17] . There was a more than three-fold increase in the effect of rigosertib on neuroblastoma cells relative to the effect on bone marrow control cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent high-throughput drug screen, we identified rigosertib as a potential anti-neuroblastoma agent that displayed high selectivity towards tumor cells compared to healthy bone marrow-derived cells [17] . Recently, Kowalczyk and co-workers also showed that rigosertib can have anti-neuroblastoma effects in conventional in vitro neuroblastoma models [18] .…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate targeting DNA repair system or drugs causing DNA damage could be synthetic lethal in MYCN -driven tumors. Recent studies reveal various strategies based on N-MYC-mediated synthetic lethality, including glutaminase inhibition or glutamine deprivation ( 157 ), BCL2 inhibition ( 125 ), eliminating SKP2 complexes ( 158 ), kinesin spindle protein (KSP) inhibition ( 159 ), G9a inhibition ( 160 ), poly (ADP-ribose) polymerase (PARP) inhibition ( 161 , 162 ).…”
Section: Synthetic Lethal Interaction With Deregulated Mycnmentioning
confidence: 99%
“…For example, the triple PIM/PI3K/mTOR inhibitor IBL-302 was used to treat an N-myc expressing neuroblastoma PDX in vivo, in combination with reduced-dose Cisplatin chemotherapy, following extensive in vitro screening [ 79 ]. A panel of MYCN -amplified neuroblastoma organoids was employed to run a high-throughput screen, selecting the inhibitor of kinesin spindle protein, ARRY-520, as an agent to cause reduced organoid viability [ 64 ]. This compound was then further tested preclinically in neuroblastoma N-myc PDX in vivo models, taken from a patient at diagnosis and at treatment-resistant relapse.…”
Section: The Development and Refinement Of Patient-derived Models For Neuroblastomamentioning
confidence: 99%
“…Additional samples may be taken from liquid biopsies, especially including bone marrow aspirates. A dedicated laboratory team should provide expertise in the engraftment of fresh tissue into immunocompromised mice, with or without the parallel establishment of patient tissue as an attached/spheroid/organoid culture [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. There are multiple considerations at this step (site of engraftment [ 46 , 55 , 56 , 57 , 59 , 60 , 72 ] strain [ 39 , 40 ]), and experimental protocols should be guided by the ultimate aims of the study.…”
Section: Figurementioning
confidence: 99%